Status Nasab dan Kewarisan Anak Hasil Sewa Rahim Perspektif Hukum Islam - Honainah Honainah; Dominikus Rato; Dyah Ochtorina Susanti (Rechtenstudent, 2023)
This study discusses the intricacies of renting a uterus, starting from the law on renting a uterus, the status of children from renting a uterus to inheritance to children from renting a uterus. This research includes the type of normative legal research (legal research) or also known as doctrinal research. The approach used in this study is a statutory approach and a conceptual approach. Analysis of legal material sources is carried out descriptively by not testing theory, but analyzing legal concepts that include legal understanding, legal norms and the legal system. The results of the study concluded that the lineage status of children born by renting a womb is that there are differences of opinion among scholars, some define the mother who owns the ovum as the real mother (nasab) and the mother who owns the uterus as a suckling mother, some other Ulama define the mother who owns the uterus as the lineage mother and the surrogate mother. owner of the uterus as a nursing mother. The inheritance of IVF children through uterine rent in Islamic law still has differences, including some Islamic law experts who say that IVF children through uterine rent are invalid because basically IVF is unlawful and as a result the child's lineage is only related to the mother who gave birth to him, after his ancestry is known, then by law inheritance follows the mother who gave birth, then between children born through IVF through renting a uterus and the mother who gave birth can inherit each other, on the basis that the woman who is pregnant and gives birth.